CREATING PROFILE PT. WATERWAY ADVERTISING USING MACROMEDIA FLASH MX - Yudhi Supriadi; Hariyanto Hariyanto, S. Kom, MMSI (Jurnal Sistem Informasi, 2005)
PT. Advertising Waterway classified as a new company, to try to expand its businessin a way promote using various media. In this Scientific Writing, writers want tointroduce one way promote PT. Waterway Advertising using the media CD (CompactDisk) The author uses Macromedia Flash MX program with the goal of keeping thecontents of the CD Profile PT. Waterway Advertising becomes more alive with thestuffed element of animation, sound, and video clips to be more interesting campaign.